Integrated Hypothalamic Transcriptome Profiling Reveals the Reproductive Roles of mRNAs and miRNAs in Sheep - Zhang, Zhuangbiao; Tang, Jishun; Di, Ran; Liu, Qiuyue; Wang, Xiangyu; Gan, Shangquan; Zhang, Xiaosheng; Zhang, Jinlong; Chu, Mingxing; Hu, Wenping (Frontiers in Genetics, 2020)
Early studies have provided a wealth of information on the functions of microRNAs, however, less is known regarding their functions in hypothalamus involved in sheep reproduction. To explore the potential roles of mRNAs and miRNAs in sheep (FecB++) hypothalamus, totally, 172 and 235 differentially expressed genes (DEGs) and 42 and 79 differentially expressed miRNAs (DEmiRNAs) were identified using RNA sequencing in polytocous sheep in the follicular phase versus monotocous sheep in the follicular phase (PF vs. MF), and polytocous sheep in the luteal phase versus monotocous sheep in the luteal phase (PL vs. ML), respectively. We also identified several key mRNAs (e.g., POMC, GNRH1, PRL, GH, TRH, and TTR) and mRNA-miRNAs pairs (e.g., TRH coagulated by oar-miR-379-5p, oar-miR-30b, oar-miR-152, oar-miR-495-3p, oar-miR-143, oar-miR-106b, oar-miR-218a, oar-miR-148a, and PRL regulated by oar-miR-432) through functional enrichment analysis, and the identified mRNAs and miRNAs may function through influencing GnRH activities or nerve cell survival associated with reproductive hormone release via direct or indirect ways. This study represents an integral analysis between mRNAs and miRNAs in sheep hypothalamus, and provide a valuable resource for elucidating sheep prolificacy.